Analisis Efisiensi Multiple Tray Aerator dalam Penurunan Kadar Fe dan Mn Air Sumur (Studi Kasus: Desa Kureksari, Sidoarjo) - Fanesa Fathimah Zahroh; Raden Kokoh Haryo Putro (Jurnal Serambi Engineering, 2024)
Various technologies are currently being introduced with the aim of simplifying access and processes to make life more comfortable for society. In order to improve people's needs, particularly in terms of drinking water, one recommended treatment technology is the multiple tray aerator. Studies of tray levels show that Fe and Mn levels decrease with higher tray levels. However, the diameter of the tray hole was the focus of the authors' research. The tray holes have a diameter of 5 mm and a distance of 6 mm between them (d = 5 mm, x = 6 mm) and the tray holes have a diameter of 7 mm and a distance of 10 mm between them (d = 7 mm, x = 10 mm) as variations. According to the research conducted, a smaller tray hole diameter will result in a high level of efficiency for reducing iron and manganese levels, 17.26% and 30.80% respectively. This means that the tray diameter can influence the efficiency of Fe and Mn reduction.